Low‐Temperature Potassium Batteries Enabled by Electric and Thermal Field Regulation. (6th March 2023) - Liu, Yanfang; Shi, Yating; Gao, Caitian; Shi, Zude; Ding, Hongbo; Feng, Yanhong; He, Yongmin; Sha, Junwei; Zhou, Jiang; Lu, Bingan
Abstract: Recharging batteries operate at sub‐zero temperature is usually limited by the slow ion diffusion and uneven charge distribution at low temperature. Here, we report a strategy to regulate electric field and thermal field simultaneously, creating a fast and uniform deposition surroundings for potassium ion in potassium metal batteries (PMBs). This regulation is achieved by using a highly ordered 1D nanoarray electrode which provides a dense and flat surface for uniforming the electric field and high thermal conductivity for reducing the temperature fluctuation. Consequently, this electrode could achieve high‐areal capacity of 10 mAh cm −2 . Besides, the dependence of potassium nucleation on temperature is unveiled. Furthermore, a full‐cell could steady operate with over 80 % of its room‐temperature capacity at −20 °C. Those respectable performances demonstrate that this strategy is valid, potentially providing guidelines for the rational design of advanced electrodes toward PMBs. Abstract : A dual regulation strategy of electric and thermal field in Potassium metal battery is realized by a highly ordered 1D CNT nanoarray. This unique electrode not only provides uniform K ion flux distribution, but also reduces the thermal fluctuation, therefore, enabling PMBs to work at low temperature.